2020
DOI: 10.1038/s41598-020-72391-y
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Ppz1 protein phosphatase toxicity involves the alteration of multiple cellular targets

Abstract: Control of the protein phosphorylation status is a major mechanism for regulation of cellular processes, and its alteration often lead to functional disorders. Ppz1, a protein phosphatase only found in fungi, is the most toxic protein when overexpressed in Saccharomyces cerevisiae. To investigate the molecular basis of this phenomenon, we carried out combined genome-wide transcriptomic and phosphoproteomic analyses. We have found that Ppz1 overexpression causes major changes in gene expression, affecting ~ 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 99 publications
(134 reference statements)
4
39
0
Order By: Relevance
“…We also show here that the G2A mutant retains most of the characteristic toxicity of native Ppz1 when overexpressed. This suggests that the major targets for Ppz1 toxicity do not localize at the plasma membrane, a hypothesis that fits well with our recent proposal that Ppz1 overexpression negatively impinges the protein translation process [28] and with the identification of two major cytosolic protein kinases, Snf1 and Hog1, as likely targets for the development of Ppz1 toxicity [26].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We also show here that the G2A mutant retains most of the characteristic toxicity of native Ppz1 when overexpressed. This suggests that the major targets for Ppz1 toxicity do not localize at the plasma membrane, a hypothesis that fits well with our recent proposal that Ppz1 overexpression negatively impinges the protein translation process [28] and with the identification of two major cytosolic protein kinases, Snf1 and Hog1, as likely targets for the development of Ppz1 toxicity [26].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the accumulation of unbudded cells expressing the Ppz1:2 chimera was indistinguishable from those expressing Ppz1 whereas, as mentioned above, cultures of cells bearing Ppz2 did not show alteration in the percentage of unbudded cells (Figure 2C). In addition, the recently reported beneficious effect on growth of the gcn2 [28] and hog1 [26] mutations in cells overexpressing native Ppz1 was mimicked in cells expressing the Ppz1:2 hybrid phosphatase (Figure S2). When the expression of these hybrid versions was investigated, we observed that none of them matched that of Ppz1, but while that of Ppz2:1 was very low, the expression of Ppz1:2 was similar to that observed for Ppz2.…”
Section: The N-terminal Region Of Ppz Phosphatases Is Relevant For Toxicitymentioning
confidence: 74%
See 3 more Smart Citations